Study on stability of a novel binder system based on palm stearin in metal injection moulding application / Muhammad Hussain Ismail ... [et al.] - Ismail, Muhammad Hussain; Muhamad, Norhamidi; Jumahat, Aidah; Subuki, Istikamah; Omar, Mohd Afian (Institute of Research, Development and Commercialisation (IRDC), 2007)
Metal Injection Molding (MIM) is a wellestablished technology for manufacturing a variety of complex and small precision parts. In this paper, fundamental rheological characteristics of MIM feedstock using palm stearin are theoretically analyzed and presented. The feedstock consisted of gas atomized 316L stainless steel powder at three different particle size distributions and the binder system of palm stearin (PS) and polyethylene (PE). The powder loading used was 60vol % for all samples (monosize 16 μm, monosize 45 μm, and bimodal 16 μm + 45 μm) and the binder system of 40vol % (PS/PE = 40/60). The viscosity of MIM feedstock at different temperatures and shear rates was measured and evaluated. Results showed that, the feedstock containing palm stearin exhibited suitable rheological properties by increasing the fluidity of feedstock in MIM process. The rheological results also showed a pseudoplastic flow characteristics, which poses higher value of shear sensitivity (n) and lower value of flow activation energy (E), that are both favourable for injection molding process.